Meta-Analysis of Psychometric Measures in Autism Assessment Tools Across the Lifespan - Barnhart, Gwendolyn (British Journal of Healthcare and Medical Research, 2024)
There are a myriad of tools that are used for mental health professionals to diagnose individuals with autism/ autistic people, however, there are a lack of tools that professionals can use to assess where a person’s strengths and challenges lie. The purpose of this meta-analysis was to garner and understanding of the measures available to providers as well as assess the limitations. Attention was focused on the sub-domains in each measure to ascertain patterns in categorical applications. A table of measures available regarding autism symptomology was created which included categorical sorting. This process was one of the first steps taken to create another measure that focused on strengths and challenges of those on the autism spectrum.